Evaluation of the pharmacological potential of N-((5-phenyl-6,11-dihydro-[1,2,4]triazolo[1’,5’:1,6]pyrido[3,4-b]indol-2-yl)methyl)benzamides - S. O. Fedotov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2025)
The rational design of new biologically active compounds is based on the use of effective structural fragments, capable of ensuring high biosimilarity, favorable pharmacokinetic properties and an appropriate safety profile. Among them, 1,2,4-triazole and indole cores occupy a special place, being widely represented in pharmacologically active molecules due to their ability to participate in various types of molecular interactions. The combination of 1,2,4-triazole and indole fragments within a single molecule promotes the creation of conjugated systems with potentially multifunctional activity, thereby expanding the opportunities for the discovery of new therapeutic agents. Early-stage computer-based prediction of toxicological and pharmacokinetic properties remains a key strategy for optimizing the screening process. The application of in silico methods allows timely assessment of the safety, ADME profile and biological potential of compounds prior to experimental investigations.